EDITORIAL: Captive to a political elite - David Robie (Asia Pacific Network, 2013)
This edition of Pacific Journalism Review is themed on the Media and Democracy in the South Pacific symposium held in Suva in September 2012. Hosted by the University of the South Pacific, the conference has provided most of the core papers for this issue, marking close to two decades of an independent research role in the region by this journal. The 2012 symposium followed two previous conferences held at AUT University in Auckland and USP in Suva in December 2010, covering topics ranging from investigative journalism and technology, peace journalism, democracy, social cohesion and various related themes.